OPTIMALKAN KEUNTUNGAN MENGGUNAKAN PROGRAM LINEAR DENGAN METODE SIMPLEKS PADA PRODUKSI DONAT KYUS - Palahudin Palahudin; Muhamad Rizki Akbar; Khomsah Kamilah; Andini Anastasia; Rismawati Rismawati; Firmansyah Firmansyah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to optimize the profit of donut production at UMM Donat Kyus through the application of the simplex method. By using a linear programming approach, this study analyzes the most effective combination of donut production to maximize profits. Research data were obtained through interviews and direct observation of the donut production process, including the amount of raw materials, production time, production costs, production capacity, and profit per day. The results showed that the optimal production combination was 46 pcs of potato donuts and 29 pcs of regular donuts per day, which has the potential to generate profits between IDR 100,000 to IDR 140,000 per day. This study highlights the importance of effective resource management in achieving maximum profits at UMKM Donat Kyus. These findings provide significant implications for production decision making in similar UMKM, so that it can increase business efficiency and profitability